Harmony Perception in Prelingually Deaf, Juvenile Cochlear Implant Users - Zimmer, Victoria; Verhey, Jesko L.; Ziese, Michael; Böckmann-Barthel, Martin (Frontiers in Neuroscience, 2019)
Prelingually deaf children listening through cochlear implants (CIs) face severe limitations on their experience of music, since the hearing device degrades relevant details of the acoustic input. An important parameter of music is harmony, which conveys emotional as well as syntactic information. The present study addresses musical harmony in three psychoacoustic experiments in young, prelingually deaf CI listeners and normal-hearing (NH) peers. The discrimination and preference of typical musical chords were studied, as well as cadence sequences conveying musical syntax. The ability to discriminate chords depended on the hearing age of the CI listeners, and was less accurate than for the NH peers. The groups did not differ with respect to the preference of certain chord types. NH listeners were able to categorize cadences, and performance improved with age at testing. In contrast, CI listeners were largely unable to categorize cadences. This dissociation is in accordance with data found in postlingually deafened adults. Consequently, while musical harmony is available to a limited degree to CI listeners, they are unable to use harmony to interpret musical syntax.